The future costs of OPV - A bottom-up model of material and manufacturing costs with uncertainty analysis - Gambhir,A; Sandwell,P; Nelson,J (Solar Energy Materials and Solar Cells, 2016)
Organic photovoltaic (OPV) technology has the potential to provide cheap solar electricity, given advances in low-cost production and module efficiency and lifetime. However, several uncertainties remain in terms of the future costs of OPV modules, which depend on future material and manufacturing costs, as well as key performance characteristics. This assessment takes an engineering-based approach to assessing the potential future cost of each component of OPV modules, as well as the future scale of OPV production plants and associated scale economies, using stochastic analysis to account for uncertainty. The analysis suggests that OPV module costs could fall within a (interquartile) range of US$0.23–0.34/Wp, with a median cost estimate of US$0.28/Wp in the near-term, with future costs most sensitive to manufacturing scale, cell efficiency and module fill factor. This compares to a projected range of module costs for more established PV technologies (crystalline silicon, cadmium telluride and copper indium gallium selenide) of US$0.35–0.6/Wp by 2020. In levelised cost of electricity terms, OPV could compete with the established technologies in both roof- and ground-mounted systems if it can achieve a 10-year lifetime.